2020
DOI: 10.1016/j.concog.2020.102879
|View full text |Cite
|
Sign up to set email alerts
|

A gist orientation before retrieval impacts the objective content but not the subjective experience of episodic memory

Abstract: A gist retrieval-orientation decreases one's ability to remember objective details from past experiences. Here, we examined whether a gist retrieval-orientation manipulation can impact both the objective and subjective aspects of remembering. Young participants took part in two cued-recollection tasks in which they studied pictures associated with labels; at retrieval, from the labels, they evaluated the vividness of their memories of the corresponding pictures, and recalled picture details. Before retrieval, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Using these measures, it was shown that the intensity of memory vividness was significantly predicted both by spatial source memory accuracy (Folville, D'Argembeau, et al, 2020b) and the number of retrieved memory details (Folville et al, 2021;Folville, D'Argembeau, et al, 2020b, 2020a. Interestingly, the positive relation between vividness and memory content extends to memory studies conducted outside the laboratory, with young participants' vividness ratings being related to the amount of recollected units of experience from real-life events (Folville, Jeunehomme et al, 2020).…”
Section: The Cognitive Bases Of Memory Vividnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Using these measures, it was shown that the intensity of memory vividness was significantly predicted both by spatial source memory accuracy (Folville, D'Argembeau, et al, 2020b) and the number of retrieved memory details (Folville et al, 2021;Folville, D'Argembeau, et al, 2020b, 2020a. Interestingly, the positive relation between vividness and memory content extends to memory studies conducted outside the laboratory, with young participants' vividness ratings being related to the amount of recollected units of experience from real-life events (Folville, Jeunehomme et al, 2020).…”
Section: The Cognitive Bases Of Memory Vividnessmentioning
confidence: 99%
“…Results revealed that regression values significantly differed from zero, thus suggesting that the intensity of memory vividness was determined by how low-level visual features were reinstated . Other recent studies have used mixed-effects models to examine the relationship between the intensity of memory vividness and the associated number of retrieved details (Folville, D'Argembeau et Bastin, 2020b, 2020a. While both linear regressions conducted within each participant and mixed-effects analyses consider the dependent and independent variables at the trial level, mixed-effects models offer the advantage of considering both trials and participants as random effects (Baayen et al, 2008).…”
Section: The Cognitive Bases Of Memory Vividnessmentioning
confidence: 99%
“…We have emphasized earlier that normal aging decreases the capacity to recollect the specific details of past experience while not affecting memory for the general meaning of previously encoded information (Flores et al, 2017;Gallo et al, 2019). A limitation of the free-recall approach that we have used in our previous studies linking vividness and episodic details is that it does not provide any insight about the capacity of participants to reinstate the gist of the memory trace (Folville, D'Argembeau et al, 2020a). One may thus wonder whether older adults could rely more than young adults on the gist of the memory trace to judge its vividness, hence reducing the intensity of the relationship between vividness and the amount of recalled specific details.…”
Section: Do Older Adults Use Episodic Details In a Similar Way As Young Adults To Frame Their Subjective Sense Of Memory Vividness?mentioning
confidence: 95%
“…Episodic memory, defined as the capacity to retrieve details of personal past events ( 1 ), is often sub-categorized as either a form of verbal memory (e.g., accurately recalling when you last spoke to a friend; objective episodic memory); or as the retrieval of detailed, integrated, and personally relevant past events [e.g., recalling the sensory, affective, and contextual details of when you last spoke to a friend; subjective episodic memory; ( 2 )]. Deficits in subjective episodic memory are associated with a tendency to overlook specific contextual details in favor of overgeneralizing experiences into a single theme or central meaning ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…To test whether more frequent cannabis use is associated with deficits in subjective episodic memory, we compared event retrieval responses (i.e., reward and specificity ratings) between those with low to moderate relative to high frequency cannabis use patterns following an ESI intervention or an ESI control condition. We hypothesized that ( 1 ) those who used cannabis more frequently would retrieve less specific and rewarding events relative to those with less frequent use, and ( 2 ) that ESI would enhance specificity and reward ratings relative to ESI control. Lastly, we examined whether there was a significant interaction between ESI condition and frequency of use groups (low to moderate vs. high) such that ESI would enhance subjective episodic memory measures to a greater extent in high frequency relative to low to moderate frequency cannabis users.…”
Section: Introductionmentioning
confidence: 99%